Lỗi: Trang web OLM.VN không tải hết được tài nguyên, xem cách sửa tại đây.

Hỏi đáp bài tập

\(\Rightarrow A=\frac{\left(2011^{2011}-3\right)+3}{2011^{2011}-3}=1+\frac{3}{2011^{2011}-3}\)

\(\Rightarrow B=\frac{2011^{2011}-1+3}{2011^{2011}-1}=1+\frac{3}{2011^{2011}-1}\)

Vì 20112011 - 3 < 20112011 - 1 =>\(\frac{3}{2011^{2011}-3}>\frac{3}{2011^{2011}-1}\)

\(\Rightarrow1+\frac{3}{2011^{2011}-3}>1+\frac{3}{2011^{2011}-1}\) hay A > B

Đọc tiếp...

Tài trợ


sin cos tan cot sinh cosh tanh
Phép toán
+ - ÷ × = ∄ ± ⋮̸
α β γ η θ λ Δ δ ϵ ξ ϕ φ Φ μ Ω ω χ σ ρ π ( ) [ ] | /

Công thức: